2021
DOI: 10.3389/fpls.2021.596927
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental LED Lighting Effectively Enhances the Yield and Quality of Greenhouse Truss Tomato Production: Results of a Meta-Analysis

Abstract: Intensive growing systems used for greenhouse tomato production, together with light interception by cladding materials or other devices, may induce intracanopy mutual shading and create suboptimal environmental conditions for plant growth. There are a large number of published peer-reviewed studies assessing the effects of supplemental light-emitting diode (LED) lighting on improving light distribution in plant canopies, increasing crop yields and producing qualitative traits. However, the research results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 111 publications
(156 reference statements)
0
16
0
Order By: Relevance
“…Additional LED light is known to positively affect several quality attributes of tomatoes, although some inconsistencies among published research have been shown, probably determined by different environmental conditions and genotypes [39,49]. On ripe fruits, a significant increase in antioxidant capacity and phenol content in the LED-treated fruits was observed in spring, but no significant differences between lighting treatments was detected in the summer (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…Additional LED light is known to positively affect several quality attributes of tomatoes, although some inconsistencies among published research have been shown, probably determined by different environmental conditions and genotypes [39,49]. On ripe fruits, a significant increase in antioxidant capacity and phenol content in the LED-treated fruits was observed in spring, but no significant differences between lighting treatments was detected in the summer (Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…In winter, the lower seasonal lighting conditions cause decreases in the yield, size, and quality of fruits. Thus, supplemental lighting is commonly used in the Northern Hemisphere to compensate for low sunlight intensity and short daylength 7,8 . In addition, greenhouse crops undergo uneven light distribution along the canopy due to self‐ and mutual‐shading.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, red LEDs (660 nm) were used with blue fluorescent lamps for lettuce, potato, spinach, and wheat in response to the need to develop better light sources for vertical and stratified crop growth systems 5 . Today, LED-based systems have been developed for plant physiology experiments 6 , suitable for research applications (in growth chamber) 7 , supplementation of lighting 8 , and adjustment of Photoperiod 9 . Artificial light and special light spectra in the greenhouse under stress conditions can be used to investigate the effects of specific spectra on plant tolerance under stress conditions.…”
Section: Introductionmentioning
confidence: 99%